Homogenization of degenerate nonlinear Dirichlet problems in perforated domains of general structure - Larin, D.V. (Нелинейные граничные задачи, 2000)
It is considered a family of boundary value problems for degenerate nonlinear elliptic second order equations in divergence form in a sequence of domains Ω⁽ˢ⁾ ⊂ Ω ⊂ Rⁿ, s = 1,2, ... .